Multimodality depiction of findings in branchio-oto-renal syndrome: two case reports - Williams, Lelia E (Acta Radiol Open, 2019)
Branchio-oto-renal syndrome is a rare genetic disorder that affects multiple organ systems. Temporal bone abnormalities include the unwound appearance of the cochlea which is common in this syndrome. This appearance can prompt renal imaging and evaluation. Presented here are two cases of branchio-oto-renal syndrome with dysplastic cochleae. A branchial cleft sinus and renal dysplasia were also present in one of the cases.